Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.cmi.2020.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Clonal spread of macrolide-resistant Mycoplasma pneumoniae sequence type-3 and type-17 with recombination on non-P1 adhesin among children in Taiwan

Abstract: Objectives: Mycoplasma pneumoniae is currently the most commonly detected bacterial cause of childhood community-acquired pneumonia in several countries. Of note, clonal expansion of macrolideresistant ST3 occurred in Japan and South Korea. An alarming surge in macrolide resistance complicates the treatment of pneumonia. We aimed to evaluate the clinical manifestation and clonal relatedness of M. pneumoniae circulating among children in Taiwan. Methods: We prospectively enrolled 626 children with radiologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Taken together, we deduced that the present high rates of MRMP with type M4572 predominantly resulted from a rapid clonal dissemination of MRMP strains of this type. Likewise, clonal expansion of macrolide-resistant strains of a specific type has also been reported in Hong Kong , Taiwan (Hung et al, 2020), Japan (Suzuki et al, 2017), and South Korea (Lee et al, 2018). Given that type M3562 is currently increasing in several countries, measures should be taken to prevent the global expansion of this clone.…”
Section: Discussionmentioning
confidence: 97%
“…Taken together, we deduced that the present high rates of MRMP with type M4572 predominantly resulted from a rapid clonal dissemination of MRMP strains of this type. Likewise, clonal expansion of macrolide-resistant strains of a specific type has also been reported in Hong Kong , Taiwan (Hung et al, 2020), Japan (Suzuki et al, 2017), and South Korea (Lee et al, 2018). Given that type M3562 is currently increasing in several countries, measures should be taken to prevent the global expansion of this clone.…”
Section: Discussionmentioning
confidence: 97%
“…1,9,11,12 A recent study, which mainly enrolled children in northern Taiwan, showed a high MR rate of up to 77% between 2017 and 2019. 10 We found that the MR rates varied greatly during our study period. M. pneumoniae infection is known to occur in cyclical epidemic periods, and macrolide resistance has been variable within individual regions over the decade these studies span.…”
Section: Discussionmentioning
confidence: 59%
“…The research groups from the Linkou Chang Gung Children's Hospital showed that the prevalence of MR-MPP in children was 12.3% in 2011 and 77% during 2017e2019. 9,10 The prevalence of MR-MPP was 18e30% from 2010 to 2017, as reported by research groups from the National Taiwan University Hospital in Taipei city. 1,11,12 The distance between northern and southern Taiwan is approximately 300 km.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Second, potential viral or bacterial coinfection was not investigated in our study. The coinfection rate with M pneumoniae is approximately 20% in some studies, the most common of which is human rhinovirus [ 31 , 32 ]. Third, pathogen detection and comparison of clinical features of the other 151 patients with positive serum M pneumoniae IgM report but negative M pneumoniae PCR or culture report were not further analyzed.…”
Section: Discussionmentioning
confidence: 99%